Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{x}{y+z}+\frac{y}{x+z}+\frac{z}{x+y}=1\)
\(\Rightarrow\frac{x\left(x+y+z\right)}{y+z}+\frac{y\left(x+y+z\right)}{x+z}+\frac{z\left(x+y+z\right)}{x+y}=x+y+z\)
\(\Rightarrow\frac{x^2}{y+z}+x+\frac{y^2}{x+z}+y+\frac{z^2}{x+y}+z=x+y+z\)
\(\Rightarrow\frac{x^2}{y+z}+\frac{y^2}{z+x}+\frac{z^2}{x+y}=0\)
\(\Rightarrow M=2019+0=2019\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Vì \(\frac{x}{y+z}+\frac{y}{z+x}+\frac{z}{x+y}=1\)
\(\Rightarrow\left(x+y+z\right)\left(\frac{x}{y+z}+\frac{y}{z+x}+\frac{z}{x+y}\right)=x+y+z\)
\(\Leftrightarrow\frac{x^2}{y+z}+\frac{xy}{z+x}+\frac{zx}{x+y}+\frac{xy}{y+z}+\frac{y^2}{z+x}+\frac{yz}{x+y}+\frac{zx}{y+z}+\frac{yz}{z+x}+\frac{z^2}{x+y}=x+y+z\)
\(\Leftrightarrow\left(\frac{x^2}{y+z}+\frac{y^2}{z+x}+\frac{z^2}{x+y}\right)+\left(\frac{xy+yz}{z+x}\right)+\left(\frac{yz+zx}{x+y}\right)+\left(\frac{zx+xy}{y+z}\right)=x+y+z\)
\(\Leftrightarrow\left(\frac{x^2}{y+z}+\frac{y^2}{z+x}+\frac{z^2}{x+y}\right)+\frac{y\left(z+x\right)}{z+x}+\frac{z\left(x+y\right)}{x+y}+\frac{x\left(y+z\right)}{y+z}=x+y+z\)
\(\Leftrightarrow\frac{x^2}{y+z}+\frac{y^2}{z+x}+\frac{z^2}{x+y}+x+y+z=x+y+z\)
\(\Leftrightarrow\frac{x^2}{y+z}+\frac{y^2}{z+x}+\frac{z^2}{x+y}=0\)
\(\Rightarrow M=2019\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Từ \(\frac{x}{y-z}+\frac{y}{z-x}+\frac{z}{x-y}=0\Rightarrow\frac{x}{y-z}=-\frac{y}{z-x}-\frac{z}{x-y}\)
\(\Rightarrow\frac{x}{y-z}=\frac{y}{x-z}+\frac{z}{y-x}\)
\(\Leftrightarrow\frac{x}{y-z}=\frac{y\left(y-x\right)+z\left(x-z\right)}{\left(x-z\right)\left(y-x\right)}\)
\(\Leftrightarrow\frac{x}{y-z}=\frac{y^2-xy+zx-z^2}{\left(x-z\right)\left(y-x\right)}\)
\(\Leftrightarrow\frac{x}{\left(y-z\right)^2}=\frac{y^2-xy+zx-z^2}{\left(x-z\right)\left(y-x\right)\left(y-z\right)}\)
C/m tương tự đc \(\frac{y}{\left(z-x\right)^2}=\frac{z^2-yz+xy-x^2}{\left(x-z\right)\left(y-z\right)\left(y-z\right)}\)
\(\frac{z}{\left(x-y\right)^2}=\frac{x^2-xz+zy-y^2}{\left(x-z\right)\left(y-x\right)\left(y-z\right)}\)
Khi đó \(Q=\frac{y^2-xy+xz-z^2+z^2-yz+xy-x^2+x^2-xz+yz-y^2}{\left(x-z\right)\left(y-x\right)\left(y-z\right)}=0\)
Vậy Q=0
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\frac{1}{x}+\frac{1}{y}+\frac{1}{z}=\frac{1}{x+y+z}\)=> \(\frac{xy+yz+zx}{xyz}=\frac{1}{x+y+z}\)
=> (x+y+z)(xy+yz+zx) = xyz
=> \(x^2y+xy^2+y^2z+yz^2+zx^2+z^2x+2xyz=0\)
=> (x+y)(y+z)(z+x) = 0
=> \(\left[{}\begin{matrix}x=-y\\y=-z\\z=-x\end{matrix}\right.\)
TH1: x = -y
=> \(\frac{1}{x^{2019}}+\frac{1}{y^{2019}}+\frac{1}{z^{2019}}=\frac{1}{\left(-y\right)^{2019}}+\frac{1}{y^{2019}}+\frac{1}{z^{2019}}=\frac{1}{z^{2019}}\)
=> \(\frac{1}{x^{2019}+y^{2019}+z^{2019}}=\frac{1}{\left(-y\right)^{2019}+y^{2019}+z^{2019}}=\frac{1}{z^{2019}}\)
=> ĐPCM
Tương tự với TH2 và TH3